Free Will and Divine Sovereignty in Eusebius of Emesa: A Fourth-Century Antiochene Homily Against Determinism - José Cebrián Cebrián (Religions)
This study examines Eusebius of Emesa’s De arbitrio, voluntate Pauli et Domini passione (Homily I), a fourth-century homily rediscovered in the twentieth century, to elucidate its contribution to the theological debate on free will within early Christianity. While Eusebius, a bishop of the Antiochene school, has been historically overlooked, his homily offers a nuanced defence of human moral agency against the deterministic paradigms prevalent in late antiquity. Through a critical analysis of the text, focusing on key biblical episodes—the conversion of St Paul, the election of Jeremiah and Jacob, and the hardening of Pharaoh’s heart—this article demonstrates how Eusebius reconciles divine sovereignty with free will by prioritising literal exegesis and emphasising humanity’s God-given capacity for self-determination. The methodology combines close textual analysis with contextualisation within broader theological controversies, particularly addressing Stoic fatalism, Gnostic predestination, and Manichaean dualism. The results reveal that Eusebius’s arguments, though pastoral in intent, are philosophically rigorous, asserting that free will underpins moral responsibility and virtue, while Christ’s voluntary Passion exemplifies divine respect for human freedom. The study concludes that Eusebius’s homily not only refutes deterministic worldviews, but also affirms free will as a theological cornerstone, bridging scriptural interpretation and doctrinal orthodoxy.